Signal measurement and estimation techniques for micro and nanotechnology - Clevy, Cedtric; Rakotondrabe, Micky; Chaillet, Nicolas; SpringerLink (Online service). (New York Springer, 2011)
Signal Measurement and Estimation Techniques for Micro and Nanotechnology discusses micro, nano and robotic cells and gives a state-of-the-art presentation of the different techniques and solutions to measure and estimate signals at the micro and nano scale. New technologies and applications such as micromanipulation (artificial components, biological objects), micro-assembly (MEMS, MOEMS, NEMS) and material and surface force characterization are covered. The importance of sensing at the micro and nano scale is presented as a key issue in control systems, as well as for understanding the physical phenomena of these systems. This book also: Explains issues that make signal measurement and estimation techniques difficult at the micro-nano-scale and offers solutions. Discusses automated micro-assembly, and control of micro-nano robotic devices Presents and links signal measurement and estimation techniques for micro-nano scale systems with microfabrication methods, sensors integration and control schemes Signal Measurement and Estimation Techniques for Micro and Nanotechnology is a must-read for researchers and engineers working in MEMS and control systems
Microscale Specificities -- Observer Techniques Applied to the Control of Piezoelectric Microactuators -- Measurement and Control for High-Speed Sub-Atomic Positioning in Scanning Probe Microscopes -- Microrobotic tools for the measurement of small forces -- Distinguishing Healthy and Defective Oocytes during Intracytoplasmic Sperm Injection -- In situ Characterizations of Thin-film Nanostructures with Large-range Direct Force Sensing -- A mechanism approach for enhancing the dynamic range and linearity of MEMS Optical Force Sensing -- Observer-based estimation of weak forces in a nanosystem measurement device
Includes bibliographical references and index
Electronic reproduction.
Keywords: Nanotechnology; Microtechnology; Information measurement